Response of tomato (Solanum lycopersicum) to varying levels of irrigation and nitrogen under trickle fertigation - SHARMA, VIKAS; CHANGADE, NITIN M; TARATE, SURYAKANT B; YADAV, B K (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted during 2022 and 2023 at Lovely Professional University, Jalandhar, Punjab to study the response of tomato (Solanum lycopersicum L.) to 3 irrigation levels [I1, 70%; I2, 85% and I3, 100% of IWR] and 3 nitrogen fertilization levels [N1, 70%; N2, 85% and N3, 100% of RDN] in split plot design. On individual effect basis, the fruit yield first increased with the increase in amount of applied irrigation water in I2 (95.6 t/ha) and then decreased in I3 (93.5 t/ha). Irrigation water use efficiency (IWUE) was the highest in I2 (3.73 t/ha-cm). Plant growth, tomato yield and IWUE were significantly higher in N2 than that were found in N1 and N3. Nitrogen use efficiency (NUE) decreased with increasing nitrogen levels (N2 and N3) but it increased with increasing amount of water applied (I3). The treatments having deficit irrigation level as I1 and I2, significantly enhanced the lycopene content (27 to 33 µg/g) and reduced the nitrate content (74 to 95 mg/kg) in the fruit over full irrigation level I3. Nitrate content was highest in N3 (100 mg/kg). Among all the combination of irrigation and nitrogen fertilization levels the interaction of I2N2 (85% of IWR and RDN) was found the best to grow the drip-irrigated tomato crop. This combination gave optimum plant growth (87.5 cm), fruit yield (100 t/ha), IWUE (3.93 t/ha-cm), NUE (0.79 t/kg) and good quality fruit. The findings can be utilized for irrigation planning and nitrogen management in tomato cultivation and to conserve available fresh water resources in water scare regions of Punjab. In order to promote trickle fertigation at village level, the awareness programs for farmers could be conducted.